The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12291-015-0516-y
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Type 2 Diabetes Mellitus

Abstract: Endothelial dysfunction is an imbalance in the production of vasodilator factors and when this balance is disrupted, it predisposes the vasculature towards prothrombotic and pro-atherogenic effects. This results in vasoconstriction, leukocyte adherence, platelet activation, mitogenesis, pro-oxidation, impaired coagulation and nitric oxide production, vascular inflammation, atherosclerosis and thrombosis. Endothelial dysfunction is focussed as it is a potential contributor to the pathogenesis of vascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 64 publications
(54 reference statements)
1
82
0
2
Order By: Relevance
“…Chronic inflammation and oxidative stress are regarded as pathophysiologic mechanisms of type 2 diabetes, which impair glucose metabolism and increase risks of other metabolic complications [15,16]. In our study, before treatment, we found indictors of inflammation including IL-6 and TNF-α increased and biomarkers of oxidative stress like MDA and SOD varied significantly in rats model.…”
Section: Discussionsupporting
confidence: 48%
“…Chronic inflammation and oxidative stress are regarded as pathophysiologic mechanisms of type 2 diabetes, which impair glucose metabolism and increase risks of other metabolic complications [15,16]. In our study, before treatment, we found indictors of inflammation including IL-6 and TNF-α increased and biomarkers of oxidative stress like MDA and SOD varied significantly in rats model.…”
Section: Discussionsupporting
confidence: 48%
“…Obesity is described to result from increased energy intake with subsequent reduced physical activities [2]. It is a metabolic condition of chronic low-grade inflammation, associated with high levels of inflammatory markers, such as CRP, IL-6, and TNF-α [2,6]. In this, the low-grade chronic inflammation is characterized by a variety of chronic diseases, including cardiovascular disease, diabetes, hypertension, nonalcoholic fatty liver disease [2], hypercholesterolemia, asthma, arthritis, some cancers, and general poor health condition, and hence represents a significant burden on the global healthcare system [5].…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of obesity increases the potential risk factors for developing chronic metabolic syndromes [7]. Significant increase in bodyweight is highly attributed to several metabolic complications, such as cardiovascular disease, pulmonary complications, diabetes, and some certain cancers [8,9], leading to diminished life expectancy [2,6]. Furthermore, overweight or obese pregnant women have increased risks of developing offspring with obesity and its other related metabolic complications in future life, which justifies a transgenerational cycle of obesity [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction is characterized by an imbalance in the production of vasodilator factors. The imbalance of these factors consequently results in vascular inflammation, disease progression, and end organ damage in T2DM . The endothelium was earlier perceived as an inactive, inert barrier between tissues and blood.…”
Section: Introductionmentioning
confidence: 99%